2008
DOI: 10.1099/ijs.0.65335-0
|View full text |Cite
|
Sign up to set email alerts
|

Oceanobacillus caeni sp. nov., isolated from a Bacillus-dominated wastewater treatment system in Korea

Abstract: A Gram-positive, rod-shaped, spore-forming bacterium, strain S-11 T , was isolated from the activated sludge of a Bacillus-dominated wastewater treatment system in South Korea and was characterized using a polyphasic approach in order to determine its taxonomic position. Cells (0.5-0.6¾2.0-2.2 mm) were motile by means of a single subpolar flagellum. They bore ellipsoidal endospores that lay in a central position in swollen sporangia. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 20 publications
3
34
0
Order By: Relevance
“…The isoprenoid quinone profiles of strain ASL-1 T and members of the two genera were similar in that the predominant menaquinone was MK-7, although strain ASL-1 T , J. alimentarius and M. campisalis contained significant amounts of . The intrageneric differences in fatty acid profiles have been reported for members of some related genera (Yoon et al, 2001a;Hanada et al, 2002;Hua et al, 2007;Nam et al, 2008). Taking into account these data, it is likely to be more reasonable that the genera Jeotgalibacillus and *Summed features represent groups of two or three fatty acids that cannot be separated by GLC with the MIDI system.…”
mentioning
confidence: 91%
“…The isoprenoid quinone profiles of strain ASL-1 T and members of the two genera were similar in that the predominant menaquinone was MK-7, although strain ASL-1 T , J. alimentarius and M. campisalis contained significant amounts of . The intrageneric differences in fatty acid profiles have been reported for members of some related genera (Yoon et al, 2001a;Hanada et al, 2002;Hua et al, 2007;Nam et al, 2008). Taking into account these data, it is likely to be more reasonable that the genera Jeotgalibacillus and *Summed features represent groups of two or three fatty acids that cannot be separated by GLC with the MIDI system.…”
mentioning
confidence: 91%
“…oncorhynchi Yumoto et al 2005), algae (O. oncorhynchi subsp. incaldanensis Romano et al 2006), an insect (O. chironomi Raats and Halpern 2007), activated sludge (O. caeni Nam et al 2008) and food (O. kapialis Namwong et al 2009). The type strains of O. oncorhynchi subsp.…”
mentioning
confidence: 99%
“…Subsequently, four Oceanobacillus species with validly published names, Oceanobacillus oncorhynchi (Yumoto et al, 2005), Oceanobacillus chironomi (Raats & Halpern, 2007), Oceanobacillus profundus (Kim et al, 2007) and Oceanobacillus caeni (Nam et al, 2008), have been reported; a further species, Oceanobacillus picturae (Lee et al, 2006), was described by the reclassification of Virgibacillus picturae (Heyrman et al, 2003). In this study, the taxonomic characterization of an Oceanobacillus-like bacterium, strain CHL-21 T , which was isolated from a marine solar saltern, is reported.…”
mentioning
confidence: 99%